Detection of bimodal survivin expressions in canine cancer types by flow cytometry compared to immunohistochemistry - Tsumoto, Shohei; Tamura, Kyoichi; Nakazawa, Yuta; Fujita, Michio; Ohkusu-Tsukada, Kozo (Frontiers in Veterinary Science, 2025)
Animal practice requires both convenience for the owner and risk management for the animal's health. Deterioration due to cancer may associate with poor prognosis under general anesthesia, which need to partial excision for pathological diagnosis. This study aimed to establish rapidly detecting the expression of survivin antigens for cancer vaccines or molecular targeted therapies via flow cytometry (FCM) using the intracellular staining method in tumor samples obtained via needle biopsy without anesthesia. Therefore, survivin expression patterns in each cell lines of canine melanomas, a murine mast cell tumor, a murine colon carcinoma, and a murine melanoma was analyzed by FCM and immunofluorescence microscopy, and compared with immunohistochemical analysis and western blot method. Interestingly, FCM results of the bimodal expression pattern of survivin were suggested to reflect the high fluorescence intensity of its nuclear–cytosol localization and the weak fluorescence intensity of its cytosol alone localization. In a case of canine cancer disease, it was confirmed that survivin expression patterns can be detected via FCM using needle biopsy samples in actual clinical settings. In this study, a novel method via FCM was proposed to quickly determine also survivin localization not only whether the survivin is expressed in cancer cells. The application of cancer vaccine or chemical therapy via this technology can be expected to contribute to improved animal care due to the “one-day first program,” which has been proposed in convenience for owners.